Genetic Diversity of ‘Candidatus Liberibacter asiaticus’ Revealed by Short Tandem Repeats and Prophage Typing Indicates Population Homogeneity in Brazil - da Silva, Priscila Alves; Fassini, Camila Giacomo; Sampaio, Laís Simões; Dequigiovanni, Gabriel; Zucchi, Maria Imaculada; Wulff, Nelson Arno [UNESP] (Scientific Societies, 2019)
‘Candidatus Liberibacter asiaticus’ is the most common huanglongbing-associated bacteria, being present in Asia, South, Central, and North America. Genomic approaches enabled sequencing of ‘Ca. L. asiaticus’ genomes, allowing for a broader assessment of its genetic variability with the application of polymerase chain reaction (PCR)-based tools such as microsatellite or short tandem repeat (STR) analysis. Although these tools contributed to a detailed analysis of strains from Japan, China, and the United States, Brazilian strains were analyzed in either too few samples with several STRs or in several strains with only a single microsatellite and a single PCR marker. We used 573 ‘Ca. L. asiaticus’ strains, mainly collected from São Paulo State (SPS), in our genetic analyses, employing three STRs and several prophage PCR markers. STR revealed a homogeneous population regardless of sampling year or geographic regions of SPS. Thirty-eight haplotypes were recognized with a predominance of VNTR_005 higher than 10 repeats, with VNTR_002 and VNTR_077 containing 11 and 8 repeats, respectively. This haplotype is indicated as class HE, which comprised 80.28% of strains. Classes HA and HB, predominant in Florida, were not found. A new genomic organization in the junction of prophages SC2 and SC1 is prevalent in Brazilian strains, indicating gene rearrangement and a widespread occurrence of a type 1 prophage as well as the presence of a type 2-like prophage. Our results indicate that ‘Ca. L. asiaticus’ populations are homogeneous and harbor a new genomic organization in prophages type 1 and 2.